Structural Versatility of 3d-Ce-Iii Heterometallic Coordination Polymers Using Co-Ii or Cu-Ii - Venegas-Yazigi, D; Venegas-Yazigi, D (American Chemical Society, 2018)
In the present work, we report the synthesis and characterization of two new heterometallic coordination polymers based on Ce-III and containing Co-II or Cu-II cations, assembled by the bifunctional ligand 1H-imidazole-4,5-dicarboxylic acid, [Ce(H2O)(2)(HIDC)Co(IDC)]center dot H2O CoCe and [Ce(H2O)(2)(H2IDC)Cu(H2O)(IDC)Cu-0.2(H1.6IDC)] CuCe. Compound CoCe was obtained under one pot hydrothermal synthesis, while CuCe was synthesized by a step-by-step synthesis using the metalloligand [Cu(H2IDC)(2)-(H2O)(2)] Cu1, as precursor. From a structural point of view, CoCe presents an intrincated 3D structure, in which alternating Lambda-Delta chiral Co-II chains can be observed, which are assembled by discrete Ce-III fragments, giving rise to the 3D structure. Meanwhile, CuCe presents a structure formed by [Cu2Ce2] heterometallic chains, partially assembled by Cu-II cations in a 2D structure. Magnetic properties reveal that both CoCe and CuCe present a global antiferromagnetic behavior, dominated by the interaction between Co-II-Co-II or Cu-II-Cu-II entities connected by mu(2)-kappa N,O-kappa O" ,N bridges, belonging to H3IDC anionic derivatives. Moreover, a weak ferromagnetic phenomenon was found in compound CoCe, corroborated by hysteresis loops and ac magnetization.